Islamic civilization through waqf institutions in Ottoman Empire between 15th until 17th century - Nur Ainul Basyirah Alias,; Shamsul Azhar Yahya,; Ermy Azziaty Rozali, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Waqf institution was a very significant building in the Islamic civilization developed by the Ottoman Empire around Eastern Europe during its rule in the 15th century until the end of the 17th century. The spread of waqf practices at that time provided many benefits and good deeds to the society including for non-Muslims. Through this institution, the Ottoman Empire gradually brought Islamic civilization into many parts of Eastern Europe. Therefore, this research focuses on the role and contribution of the waqf institutions in expanding Islamic civilization during the Ottoman Empire over the region from the 15th century to the 17th century. This study was conducted using qualitative methods in the form of historical research while data collection methods used the method of analysis of documents from various primary and secondary sources as well as using interview method to strengthen the data obtained. The results show that the Ottoman Empire not only bring Islamic civilization but spreading the Ottoman civilization as well. There is no doubt that through this institution, there was a mixing of culture occurred led to the emergence of new culture in the region. In addition, the study found that the contribution of the waqf institutions covered variousaspects such as economic, socio-cultural, educational, religious and humanitarian. In conclusion, the construction of waqf institutions had a positive impact on the society. The government not only expanded their power by conquering new territories but also wanted to spread the Islamic civilization and provide welfare to the people.